Long-Term Tree Regeneration of Fragmented Agroforestry Systems Under Varying Climatic Conditions - Díaz, Mario; Sánchez-Mejía, Teresa; Morán-López, Teresa (Frontiers in Ecology and Evolution, 2021)
Iberian dehesas and montados are agroforestry systems protected by the European Habitats Directive due to high levels of biological diversity associated to their savannah-like structure. Tree scattering in dehesas, montados and other agroforestry systems is however known to compromise tree regeneration, although recent work suggests that it may protect tree populations from climate warming by alleviating plant-plant competition. We analyse how climatic conditions, tree isolation and their interactions influence the outcomes of regeneration stages, from flower production to early seedling establishment, using data gathered during the long-term monitoring (2001- 2018) of ca. 300 Holm oak Quercus ilex located in central Spain. Holm oak reproductive effort, predispersal seed losses, and early seedling recruitment were sensitive to climate change, especially to year-round drought. Effort and early seedling recruitment decreased, while abortion and predispersal seed predation increased, with higher drought intensity. Spring warming increases pollination effectiveness, but had no further effect on acorn crops. Forest clearing seemed to have little scope to ameliorate these negative effects, as shown by weak or no interactive effects between the spatial configuration of trees (cover or isolation) and climate variables (spring temperature or drought intensity). Management options aimed at decreasing adult tree mortality under climate change scenarios would then have little or no effects on tree recruitment. Landscape-scale rotations alternating shrub encroachment and thinning along periods adapted to changing climate were proposed as the main management option to preserve both oak forests and dehesas in the long term.